Implementasi Media Pembelajaran Word Square dalam Meningkatkan Minat Baca Peserta Didik: Implementation of Word Square Learning Media to Enhance Students’ Reading Interest - Sukmawaty; Amalia Ramadhani; Nursyamsi (Universitas Mulawarman, 2025)
Education plays a crucial role in developing students' potential, with reading being a fundamental skill. However, the current teaching methods in elementary schools, often dominated by monotonous lectures, lead to a lack of interest in reading. This study investigates the use of Word Square as a learning media to enhance reading interest among fourth-grade students at SDN 51 Sumarambu. The research follows a Classroom Action Research (CAR) method with a qualitative approach, conducted in two cycles. The findings reveal that the application of Word Square media significantly improved students' reading interest. In the first cycle, the average reading interest score was 64.28%, which increased to 88.33% in the second cycle. This demonstrates that the Word Square media effectively fosters students’ engagement in reading activities, making learning more active, enjoyable, and interactive. The study concludes that Word Square is an effective tool for improving reading interest in elementary school students, contributing to a more engaging and dynamic classroom environment.